Heterogeneity of the blood-brain barrier - Wilhelm Imola Mária; Nyúl-Tóth Ádám; Suciu Maria; Hermenean Anca; Krizbai István Adorján (Landes Bioscience, 2016)
The brain microvascular network is comprised of capillaries, arterioles and venules, all of which retain - although to a different extent - blood-brain barrier (BBB) properties. Capillaries constitute the largest and tightest microvasculature. In contrast, venules have a looser junctional arrangement, while arterioles have a lower expression of P-gp. Development and maintenance of the BBB depends on the interaction of cerebral endothelial cells with pericytes and astrocytes, which are all heterogeneous in different regions of the central nervous system. At the level of circumventricular organs microvessels are permeable, containing fenestrations and discontinuous tight junctions. In addition, the blood-spinal cord barrier - where the number of pericytes is lower and expression of junctional proteins is reduced - is also more permeable than the BBB. However, much less is known about the cellular, molecular and functional differences among other regions of the brain. This review summarizes our current knowledge on the heterogeneity of the brain microvasculature.